National Steinbeck Center display
National Steinbeck Center (NSC, 1 Main Street) portrait of Rocinante, the General Motors V6 truck and Wolverine Camper Company (Glaswin, Michigan) camper that Steinbeck drove around the United States in 1960 for Travels with Charley. After the trip, Steinbeck sold the truck to William Plate, who donated it to the NSC in 1990. The truck sat in storage until 1998, when Gene Cochetti's Body Shop (Salinas) did the restoration work needed for free. From series of publicity shots. Slide only.